Black Holes and Information Paradox: Resolving the Hawking Paradox - Mrs. Monika (Innovative Research Thoughts, 2023)
The mysterious nature of black holes has fascinated scientists for decades, and its interplay with quantum physics has led to the "Information Paradox." Stephen Hawking's paradox challenges what happens to information that falls into a black hole, since it seems to contradict quantum physics' information conservation. explores the Black Hole Information Paradox and the conflict between traditional gravitational physics and quantum theory. We discover the paradox's depth and its consequences for our knowledge of spacetime and quantum states by investigating the Hawking radiation process and information preservation. Draws on current advances in string theory, quantum gravity, and entanglement principles to give a new take on the conundrum. The interaction between the event horizon, holographic principle, and non-local quantum correlations allows reconciliation. A conceptual framework implies black holes might encode and store information holographically as sophisticated quantum information processors. This proposal reimagines the event horizon as a dynamic interface that delicately integrates information into its structure, defying locality and determinism. Using the holographic principle and entanglement entropy, the dilemma is resolved harmoniously. Contributes to the discussion of black holes, quantum physics, and information conservation via careful study and multidisciplinary synthesis. Our approach gives a tantalising peek into a unified theory that transcends paradigms by reconciling gravitational collapse and quantum unitarity. However, the effects of this resolution on theoretical physics, cosmology, and reality need additional study.